A Synthesis of Thiopyran Pyridinium Perchlorate Compounds - All-Heety, Marwan F; Al-Bayati, Sameaa J; Kadhim, Mohammed A; Jesama, Rasha A (Al-Nahrain Journal of Science, 2013)
Asynthesis of four pyridinium perchlorate compounds have been prepared from reaction one mole pyrylium salt (product already) with one mole cysteine in room temp. and diagnosed spectrally (FT-IR., 1H-NMR) in addition to the accurate quantitative elemental analysis.Asynthesis of sixteen Thiopyranpyridinium perchlorate compounds from reaction one mole from pyridinium compounds produced with one mole pyrylium salt (product already) under zero temp. very good yields that were diagnosed spectrally (FT-IR., 1H-NMR) in addition to the accurate quantitative elemental analysis. Keywords: